2012
DOI: 10.1371/journal.pone.0030974
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Co-Culture with Tendons or Tenocytes Can Program Amniotic Epithelial Cells towards Stepwise Tenogenic Differentiation

Abstract: BackgroundAmniotic epithelial cells (AEC) have potential applications in cell-based therapy. Thus far their ability to differentiate into tenocytes has not been investigated although a cell source providing a large supply of tenocytes remains a priority target of regenerative medicine in order to respond to the poor self-repair capability of adult tendons. Starting from this premise, the present research has been designed firstly to verify whether the co-culture with adult primary tenocytes could be exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(126 citation statements)
references
References 65 publications
(77 reference statements)
7
119
0
Order By: Relevance
“…The HADMSC and HUVEC co-culture system was demonstrated to promote in vitro HADMSC differentiation towards tenocytes on the aligned PLLA fibrous scaffold. Some other studies also employed a co-culture technique to promote MSC differentiation, and confirmed that a co-culture of MSC and tenocytes enhanced the tenogenic differentiation of MSC [6669]. Our results indicate that the incorporation of EC may initiate the vascularization and promote tenogenesis of MSC to recapitulate the initial tendon healing process.…”
Section: Discussionsupporting
confidence: 82%
“…The HADMSC and HUVEC co-culture system was demonstrated to promote in vitro HADMSC differentiation towards tenocytes on the aligned PLLA fibrous scaffold. Some other studies also employed a co-culture technique to promote MSC differentiation, and confirmed that a co-culture of MSC and tenocytes enhanced the tenogenic differentiation of MSC [6669]. Our results indicate that the incorporation of EC may initiate the vascularization and promote tenogenesis of MSC to recapitulate the initial tendon healing process.…”
Section: Discussionsupporting
confidence: 82%
“…For the co-culture investigations, 2x10 5 OCSCs were seeded with an equal number of human PBMC-derived macrophages (2x10 5 ) on day 7 of culture and then cultured for a further 3 days in RPMI-1640 medium. For the Transwell co-culture, cultivation was performed, as described previously (23). Briefly, 0.4 µm pore-size Corning Transwell inserts (VWR International, Inc., West Chester, PA, USA) were placed into 6-well plates with 2x10 5 macrophages, initially seeded at the bottom of the chamber and 2x10 5 OCSCs seeded onto the inserts, followed by culture for a further 3 days (24).…”
Section: Methodsmentioning
confidence: 99%
“…cytokeratin 8 (epithelial marker) and alpha smooth muscle actin (α-SMA: mesodermal marker), expression by immunocytochemistry [46];…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemical analyses were carried out on freshly isolated, expanded and thawed oAEC as previously described [46]. Briefly, cells were fixed in 4% paraformaldehyde in phosphate buffered saline solution (PBS) and permeabilized with 0.1% Triton X-100/PBS.…”
Section: Methodsmentioning
confidence: 99%